A Survey of Investors Preference on Stock Market : A Case of Nepal Stock Exchange - Pokharel, Post Raj (Saptagandaki Journal, 2018)
This paper shows investors preference on stock market of Nepal Stock Exchange (NEPSE). The study is based on survey method using structured questionnaire. The results demonstrated that investors were found to have investment interest in secondary market. The reasons for selecting shares are mostly liquidity and high rate of earning. The investors' perception regarding the influencing factors for the investment decision in secondary market of NEPSE is the advice of brokers and then movement of indices. The news in daily newspaper and market sentiments are viewed as least influencing factors for investment decision. Most motivating factors prioratized by respondents were capital gains, then liquidity and then dividend, safety and bonus shares. The motivating factors like tax benefits and rights shares were under least preference by the respondents. The Sapta Gandaki Journal Vol. IX, 2018 Feb. Page: 53-61